IDEOLOGICAL CONFLICTS IN ENGLISH LANGUAGE TEACHING Perceptions of Nonnative English-Speaking Teachers Towards Methods and Teaching Styles of Native English-Speaking Teachers - Maraden Parlindungan Silalahi, Ronald (Proceedings of English Linguistics and Literature, 2020)
Native-is a view or a stereotype in language teaching, especially foreign languages, that relies on the belief that the most correct and appropriate method of learning English is conducted by Native English Speaking Teachers (NEST) (Holliday, 2005; Silalahi, 2019). This phenomenon has an impact on the emergence of labeling 'cultural stereotypes' and negative stigma on the quality of teaching of the non-native speaker (Wu & Ke, 2009). On the other hand, Non-NEST feels that the learning methods and styles used by NEST are not appropriate to the social and cultural context of learners. This is research which is specifically directed to analyze ideological conflict and focused on describing holistically Non-NEST perceptions of NEST teaching methods and styles. Focus Group Discussions (FGD) were conducted to be able to find out Non-NEST perceptions of the quality of NEST. The FGD was conducted with 18 informants from three different private higher educational institutions that carried out Teaching as a foreign language (TEAFL). 18 informants were divided into three groups, each consisting of 6 informants. Each informant was asked to answer and give opinions on a number of questions raised in the forum. All the answers and responses given by the informants can be used as the basis for argumentation in this study. This research is expected to be able to answer ideological problems and enrich knowledge about language ideology in the context of TEAFL.